A review of glyphosate application: the health-related effect - Joanna Rog; Paulina Wróbel-Knybel (Kazimierz Wielki University, 2019)
Introduction and purpose The glyphosate (GLY) is a systemic herbicide and cropp desiccant registered for use in more than 130 countries. The herbicide is applied to control more than 160 weeds. Despite the declarations about complete biodegradability of herbicide, is difficult to complete elimination of it. GLY may affect the activity of cytochrome P450, the gut microbiome and metals chelation and thus have an adverse health effect. The evidence suggests a relationship between the use of GLY and numerous chronic diseases. The aim of this paper was to review the available literature that examined the health-related effect of GLY. The state of knowledge Numerous studies have confirmed the adverse effects of GLY on health. GLY injection in high dose initiate processes involved in cancerogenesis. In human studies, the GLY use was related with 41% higher risk of non-Hodgkin's lymphoma. GLY can lead to endocrine changes, including corticosterone levels and steroidogenesis. In pregnant women population, the higher GLY concentrations in urine were related with shorter pregnancy length. GLY could affects gut microbiome and leading to the development of intestinal dysbiosis, gut-brain axis and central nervous system changes. The formulated complexes GLY-minerals may damage nephrons. The nephrotoxic effect of herbicide was confirmed in human studies. Conclusions Most of the studies assessed the short term health-related effect of GLY. Obtained results do not reflect the environmental exposure which lasting many years. There is an urgent need to assess the long term effect of GLY in small doses in high-quality epidemiological studies.